2021
DOI: 10.3390/nano11040839
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride (C3N4) Reduces Cadmium and Arsenic Phytotoxicity and Accumulation in Rice (Oryza sativa L.)

Abstract: The present study investigated the role of graphitic carbon nitride (C3N4) in alleviating cadmium (Cd)- and arsenic (As)-induced phytotoxicity to rice (Oryza sativa L.). A high-temperature pyrolysis was used to synthesize the C3N4, which was characterized by transmission electron microscopy, Fourier-transform infrared spectroscopy, and dynamic light scattering. Rice seedlings were exposed to C3N4 at 50 and 250 mg/L in half-strength Hoagland’s solution amended with or without 10 mg/L Cd or As for 14 days. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…15,16 Several studies have now found that the addition of g-C 3 N 4 can reduce the toxicity of heavy metals such as cadmium and arsenic in the soil through chemical and biological pathways, ensuring the normal growth of crops such as rice. 17,18 Based on these properties, we hypothesized that soil amendment of g-C 3 N 4 could promote the plant photosynthesis, antioxidant capacity, soil nutrient cycling, crop yields, etc. A recent report showed that g-C 3 N 4 can enhance the photosynthesis in maize during the seed germination period.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Several studies have now found that the addition of g-C 3 N 4 can reduce the toxicity of heavy metals such as cadmium and arsenic in the soil through chemical and biological pathways, ensuring the normal growth of crops such as rice. 17,18 Based on these properties, we hypothesized that soil amendment of g-C 3 N 4 could promote the plant photosynthesis, antioxidant capacity, soil nutrient cycling, crop yields, etc. A recent report showed that g-C 3 N 4 can enhance the photosynthesis in maize during the seed germination period.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique physicochemical characteristics, quantum effects, and large surface area, nanomaterials (NMs) have been used in many fields such as food chemistry, catalysis, , medical, , environmental, , pollution remediation, and energy. , In recent years, nanoagriculture has emerged as a potential application area for NMs. , NMs have been investigated for their possible application in agriculture as nanofertilizers, , nanopesticides, , growth regulators, biosensors, and targeted transporters. ,, With considerable advancements in the synthesis and characterization of NMs as well as a greater mechanistic knowledge of nanomaterial–plant interactions, the application of nanotechnology in agriculture has grown significantly over the past 10 years. The development of highly specialized, even responsive, nanomaterials and their fine-tuning have enormous potential as a long-term approach to agricultural enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…23 Similarly, Ma et al reported that g-C 3 N 4 significantly ameliorated Cd-and As-induced phytotoxicity to rice in hydroponics and lowered the Cd and As accumulation in rice via modulating the expression of genes associated with Cd and As transporters. 24 However, the efficacy of g-C 3 N 4 in metal(loid)-contaminated agricultural soil remains unknown, as is the associated mechanisms of action. In comparison with a hydroponic system, soil provides a more realistic environment for plant growth upon coexposure to g-C 3 N 4 and metal(loid)s. The potential interaction of g-C 3 N 4 and soil altered plant nutrient and metal(loid) uptake and subsequently affected metal(loid)-induced phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%